A Systematic Review on Clinicopathological Evaluation of Neutrophil-Percentage-To-Albumin-Ratio (NPAR): An Emerging Biomarker for Hepato-Pathology and Hepato-Oncology - Abdul Rehman Khalil Shaikh; Abdul Mannan Jehangir; Anum Usman; Durga Devi; Muhammad Akram; Muhammad Mazhar (Pakistan Journal of Medicine and Dentistry)
Background:  The Neutrophil Percentage to Albumin Ratio (NPAR) proved to be an advanced combined pathological marker for assessing hepatopathology and hepatocellular carcinoma (HCC). The diagnostic value of NPAR remained unclear because research on its clinical applications and performance in contrast to typical biomarkers remains scarce. The goal of this evaluation was to methodically analyze and assess NPAR’s role as a biomarker in the examination of hepatopathology and hepatocellular carcinoma.